Cooperative Efforts and the Stages Previous to Internationalization: The Case of Telefónica - Calvo, Ángel (2014)
This article explores an area that has received relatively little attention from economic historians in Spanish-speaking countries despite the formidable appeal of its economic, technological, regulatory, and geopolitical implications. An interdisciplinary approach is employed which employs a balanced combination of primary and secondary sources. It is framed within the gradualist approach of the Uppsala School, though without adopting all of its postulates, and analyzes Telefónica’s “internationalization before internationalization” that occurred through its participation in artificial satellites. As a result of transnational cooperative efforts, the creation of these effective systems of telecommunication sometimes included Latin American countries. The participation of Telefónica in the Spanish system of satellites coincided with the beginning of its direct foreign investment, starting in 1989 with its entry into the Chilean market.